Mutagenic Effect of Proton Beams Characterized by Phenotypic Analysis and Whole Genome Sequencing in Arabidopsis - Lee, Sang Woo; Kwon, Yu-Jeong; Baek, Inwoo; Choi, Hong-Il; Ahn, Joon-Woo; Kim, Jin-Baek; Kang, Si-Yong; Kim, Sang Hoon; Jo, Yeong Deuk (Frontiers in Plant Science, 2021)
Protons may have contributed to the evolution of plants as a major component of cosmic-rays and also have been used for mutagenesis in plants. Although the mutagenic effect of protons has been well-characterized in animals, no comprehensive phenotypic and genomic analyses has been reported in plants. Here, we investigated the phenotypes and whole genome sequences of Arabidopsis M2 lines derived by irradiation with proton beams and gamma-rays, to determine unique characteristics of proton beams in mutagenesis. We found that mutation frequency was dependent on the irradiation doses of both proton beams and gamma-rays. On the basis of the relationship between survival and mutation rates, we hypothesized that there may be a mutation rate threshold for survived individuals after irradiation. There were no significant differences between the total mutation rates in groups derived using proton beam or gamma-ray irradiation at doses that had similar impacts on survival rate. However, proton beam irradiation resulted in a broader mutant phenotype spectrum than gamma-ray irradiation, and proton beams generated more DNA structural variations (SVs) than gamma-rays. The most frequent SV was inversion. Most of the inversion junctions contained sequences with microhomology and were associated with the deletion of only a few nucleotides, which implies that preferential use of microhomology in non-homologous end joining was likely to be responsible for the SVs. These results show that protons, as particles with low linear energy transfer (LET), have unique characteristics in mutagenesis that partially overlap with those of low-LET gamma-rays and high-LET heavy ions in different respects.